Acute pediatric appendicitis in black and white: clinical disparities, impact and future recommendations - Khan, Aimen Waqar; Dar, Marrium Sultan; Nabi, Rayyan; Ali, Ahmad; Humayun, Muhammad Abdullah; Riaz, Eman (Frontiers in Pediatrics, 2024)
Racial and ethnic disparities have long been studied in the delivery of healthcare. One such avenue is acute pediatric appendicitis, which continues to be an area of significant and continual research. Because of its routine clinical presentation and standardized management, acute pediatric appendicitis serves as an appropriate proxy for studying discrepancies in healthcare. Our review therefore aims to comprehensively highlight the various dimensions of its clinical management subject to disparities, their collective clinical impact, and future recommendations to mitigate it.